Melatonin as an adjunctive treatment on dental procedures: A systematic review - de Oliveira, Perdo Henrique Chaves [UNESP]; Lemos, Cleidiel Aparecido Araujo; Cantiga-Silva, Cristiane [UNESP]; Faria, Flávio Duarte [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Wiley, 2021)
The systematic review tried to answer the following question: Does the melatonin administered systemically or topically ameliorate patients involved with oral health conditions or dental procedures? The systematic review has been registered in the PROSPERO (2021CRD42021095959). Eligibility criteria included only randomized controlled clinical trials (RCTs) with at least 10 participants that compared patients that received melatonin as a treatment before and/or after their oral intervention topically or systemically, with control patients. A search was performed in PubMed/MEDLINE, Web of Science, Cochrane Library, and Academic Google databases for articles up to February 2021. The Cochrane risk-of-bias tool for randomized clinical trials was used and revealed that the studies included presented low risk of bias for the majority of criteria assessed. It was selected 25 articles, of which only six did not demonstrate positive effects and three presented null effects with the use of melatonin. Melatonin has improved the inflammatory response in periodontal disease, dental surgeries, and mucositis of head and neck oncologic irradiated patients. In addition, it showed anxiolytic potential in patients that were submitted to dental procedures. In conclusion, melatonin favored the treatment of oral changes when used topically and systemically.
Keywords: dental; melatonin; oral; procedures; treatment